Voters’ Turnout and Democratisation in Nigeria: Interrogating the 2023 Presidential Election - Hassan, Muritala Babatunde (African Journal of Stability and Development (AJSD), 2024)
The persistent trend of voters’ apathy in Nigeria remains an issue of concern to advocates of democracy and its sustenance in the country. Democracy is inherently dependent on the will of the people. The acceptability of a democratically instituted government is (to a large extent) measured by the popular support given by the people through periodic elections. This presupposes that elected representatives must regularly face the voters to seek or renew their mandates. Be that as it may, citizens’ participation in the election of their representatives underscores the substance of representative democracy. The legitimacy of emerging governments in a democratic political system is therefore hinged on the extent to which eligible voters come out to vote for them during elections. However, a worrisome phenomenon in Nigeria’s electoral history, most especially since the re-democratisation of the polity in 1999, is the declivity of voters’ turnout in both general and off-season elections. Specifically, voters’ turnout during the 2023 general elections was abysmally low. Of the 87.2 million Nigerians who collected their permanent voter’s card (PVC) out of 93.4 million who registered to vote, only 24.9 million (26.74%) actually voted during the presidential election. It is on the premise of this factuality that this paper interrogates the causes and implications of voters’ apathy for democracy and democratisation in Nigeria. Using qualitative approach, the paper examines the historical dynamics of voters’ turnout in Nigeria and its implications on democratisation, with specific reference to the 2023 presidential election.